1992
DOI: 10.1038/358169a0
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 chaperones protein folding in vitro

Abstract: The heat-shock protein Hsp90 is the most abundant constitutively expressed stress protein in the cytosol of eukaryotic cells, where it participates in the maturation of other proteins, modulation of protein activity in the case of hormone-free steroid receptors, and intracellular transport of some newly synthesized kinases. A feature of all these processes could be their dependence on the formation of protein structure. If Hsp90 is a molecular chaperone involved in maintaining a certain subset of cellular prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
292
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 496 publications
(308 citation statements)
references
References 13 publications
12
292
0
3
Order By: Relevance
“…Previously we have demonstrated that the GroE chaperone system of Escherichia coli consisting of GroEL, GroES, and ATP (Schmidt & Buchner, 1992) and eukaryotic Hsp90 (Wiech et al, 1992) influence the refolding of MAK 33 Fab. Both chaperones do not accelerate the folding process.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have demonstrated that the GroE chaperone system of Escherichia coli consisting of GroEL, GroES, and ATP (Schmidt & Buchner, 1992) and eukaryotic Hsp90 (Wiech et al, 1992) influence the refolding of MAK 33 Fab. Both chaperones do not accelerate the folding process.…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence for the role of Hsp90 in protein folding came from in vitro studies where it was demonstrated that chemically denatured substrates like citrate synthase (mainly α-helical structure) and Fab fragment of a monoclonal antibody (only β-sheets present) can be efficiently refolded with a high yield in the presence of purified Hsp90 (Wiech et al, 1992). It was also shown in vitro that Hsp90 primarily functions in preventing aggregation of stress-denatured proteins and maintains them in a folding competent state (Freeman and Morimoto, 1996;Yonehara et al, 1996).…”
Section: Ii41122 the Hsp90 Chaperone Systemmentioning
confidence: 99%
“…In eukaryotes, the cytoplasmic HSP90s act as specific chaperones for a wide range of client proteins such as the cytoplasmic receptor steroid hormones [5]. HSP90 alone can act to prevent protein aggregation and promote refolding in itro [6], but in i o it is functionally associated in multiprotein complexes with a range of associated proteins such as p23 [7], HSP70\HSP40 [8], FKBP52 [9], Hop (p60\Sti1) [10], Cdc37\p50 [11] and Cyp40 (cyclophilin 40) [12].…”
Section: Introductionmentioning
confidence: 99%